THE RELATIONSHIP OF NUTRITIONAL STATUS, HEALTH STATUS AND QUALITY OF LIFE OF THE ELDERLY IN THE ELDERLY POSYANDU PROGRAM IN BUKITTINGGI CITY - Syam, Alexander; Ramadhani, Tiara Suci; Bakri, Zamhar (Jurnal Ilmu Pendidikan Ahlussunnah, 2023)
Posyandu for the elderly is a forum for providing health services and guidance to elderly groups in an area by involving the active participation of the community through health cadres. Meanwhile, elderly people are the final stage of human life development. This period of old age is associated with a decrease in the ability to live and individual sensitivity. Important aspects that will impact the quality of life of the elderly include education and health. These two aspects are able to increase the capacity of elderly people to live in society so that they do not become a burden on society and to improve their health status. Describe the health condition and nutritional status of the elderly which can influence the strengthening of households in Bukittinggi City. This research is quantitative descriptive. This research was conducted in West Sumatra Province, especially Bukittinggi City. The population of this study was 80 elderly people. The gender of the elderly in Bukittinggi City is dominated by women at 95%. Measurement of BMI and nutritional status of the elderly in Pariaman showed that 45 respondents (57.9%) had normal nutrition and 34 respondents (42.1%) had abnormal nutrition. The implementation of the elderly health development program has not been in accordance with what implementers in the field expect. The main point is that the implementation was not adhered to by the activity implementers because it was not in accordance with their requests and the situation of the elderly Yandu group. the availability of human resources is adequate, the financing of posyandu for the elderly is inadequate, the availability of facilities and infrastructure is inadequate, the policy is in line with Law no. 36 of 2009 concerning Health article 138, the implementation of posyandu for the elderly is not yet optimal.